GOVERNMENT BORROWING AND THE LONGTERM INTEREST RATE: APPLICATION OF AN EXTENDED LOANABLE FUNDS MODEL TO THE SLOVAK REPUBLIC - Hsing, Yu (Economic Annals, 2010)
Extending the open-economy loanable funds model, this paper finds that more government borrowing as a percent of GDP leads to a higher government bond yield, that a higher real money market rate, a higher expected inflation rate, a higher EU government bond yield, or a decrease in the Slovak nominal effective exchange rate would increase the Slovak government bond yield, and that the positive coefficient of the percent change in real GDP is insignificant at the 10% level. When the standard closedeconomy or open-economy loanable funds model is considered, except that the positive coefficient of the ratio of the net capital inflow to GDP is insignificant at the 10% level, other results are similar.